The medicinal properties of clove with special focus on antimicrobial effect: a systematic review (Journal of Medical Science, 2024)
Clove, the dried flower bud of the Syzygium aromaticum tree, has been used for thousands of years in traditional medicine for its medicinal properties. One of the most well-known properties of clove is its antimicrobial activity attributed to a compound called eugenol. Eugenol has been found to be effective against a wide range of microorganisms, including bacteria, viruses, fungi, and parasites. In addition to its antimicrobial activity, clove has also been found to have anti-inflammatory, antioxidant, and pain-relieving properties. These properties make it an ideal natural remedy for a wide range of conditions, including toothaches, sore throat, and skin infections. With this background a systematic review was conducted wherein we explored the articles relevant to the research questions through databases like PubMed, Scopus, Web of Science, etc. Out of 150 articles explored, 30 were selected through online and snowballing literature searches. Out of these, 19 were original research articles, 8 systematic reviews, and 3 books/online resources . The selected articles were further assessed on quality reporting. In the current scenario of increasing prevalence of bacterial infections and emergence of multidrug resistant strains it is essential to explore alternative options like herbal antimicrobials to combat this problem.